Caring for Visually Impaired Patients in the Hospital: A Multidisciplinary Quality Improvement Project. Issue 5 (May 2020) - Carlson, Christine; Howe, Tami; Pedersen, Chase; Yoder, Linda H.
ABSTRACT: Background: People with low vision or blindness may experience anxiety, fear, and depression—sometimes severe—as a result of the challenges encountered when they seek medical care. Such patients deserve, and health care professionals must provide, equal opportunities to participate in and benefit from their health care in a safe environment. A search of the literature yielded information on the needs of visually impaired people but failed to find a comprehensive program that health care facilities could use to meet the needs of this vulnerable population. This gap in the literature on visually impaired patients (VIPs) and implications for their care led us to conduct focused meetings with this population. Objective: The specific aims of this quality improvement (QI) project were to determine the needs of hospitalized VIPs, develop educational and other resources that would help clinicians and ancillary hospital staff in their interactions with VIPs, and assemble a toolbox of useful materials for VIPs themselves. Methods: A VIP care team identified the needs of VIPs as reported in the literature and in personal meetings with visually impaired people in the community. The team also surveyed interdisciplinary hospital staff members to determine their experience in caring for VIPs as well as their educational needs, and then developed strategies and educational modules to help clinicians and ancillary staff members accommodate the unique needs of VIPs in accordance with the Americans with Disabilities Act of 1990. The team also assembled a VIP toolbox that contained several items useful to VIPs themselves. Supplementary information tailored to the function of each hospital department (such as nursing, admissions, environmental services, dietary, and radiology) was also provided to help staff members improve VIPs' hospital experience. Results: The hospital's interdisciplinary staff members participated in an education program to improve their care of VIPs. Before the program, only 23.6% of 161 staff members reported having received education on caring for VIPs. After the program, however, 56.4% of 140 staff members reported having received such education. Former patients requested bracelets and room identifiers that would alert staff members to VIPs' needs, and the team provided these. The team also introduced a braille version of the hospital menu and provided VIP toolboxes at each nursing station that contained many useful daily care items. Conclusions: VIPs have specific needs when hospitalized. Patients' and staff members' responses to this QI project were overwhelmingly positive; both groups were appreciative of the newly implemented initiatives to meet the special needs of the visually impaired. Abstract : To improve the experiences of visually impaired patients (VIPs) at their hospital, a team of nurses developed a VIP care program that included educational resources for staff and toolboxes containing daily care items for VIPs.